Kedudukan Al-Hadis dalam Perkembangan Bahasa Arab - Djamaluddin, Burhanuddin; Bimantoro, Prabu; Erizal, Erizal (AL-DZIKRA: JURNAL STUDI ILMU AL-QUR'AN DAN AL-HADITS, 2024)
AbstractThis research discusses the position and influence of Hadith in the development of the Arabic language, focusing on its impact on vocabulary, grammatical structure, stylistic elements, and specific cases. The aim of this study is to explain how Hadith affects these aspects and to highlight the implications of this influence on the culture and religious identity of Muslims. The method used is a literature review of primary and secondary sources, including authentic Hadith and analyses of Arabic literary works. The results indicate that Hadith not only enriches the Arabic language with religious vocabulary and syntactic structures but also influences the stylistic and rhetorical aspects of Arabic literature, reflecting a rich intellectual heritage within the Arab-Islamic tradition.Keywords: Arabic; Grammatical Structure; Hadith; Influence; Vocabulary. AbstrakPenelitian ini membahas bagaimana kedudukan ataupun pengaruh Hadis dalam perkembangan bahasa Arab yang fokus pengaruhnya terhadap kosakata, struktur tata bahasa, gaya bahasa, dan kasus-kasus khusus. Tujuan penelitian ini adalah untuk menjelaskan bagaimana Hadis mempengaruhi aspek-aspek ini dan menyoroti implikasi dari pengaruh tersebut terhadap budaya dan identitas keagamaan umat Islam. Metode yang digunakan adalah studi pustaka terhadap sumber-sumber primer dan sekunder, termasuk hadis-hadis sahih dan analisis literatur sastra Arab. Hasilnya menunjukkan bahwa Hadis tidak hanya memperkaya bahasa Arab dengan kosakata keagamaan dan struktur sintaksis, tetapi juga mempengaruhi gaya bahasa dan retorika sastra Arab, mencerminkan warisan intelektual yang kaya dalam tradisi Arab-Islam. Kata Kunci: Bahasa Arab; Hadis; Kosakata; Pengaruh; Struktur Tata Hahasa.